2007
DOI: 10.1007/s11745-007-3109-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fatty Acids for Chemotaxonomy of Reef‐Building Corals

Abstract: Sixteen scleractinian species of six coral families (Acroporidae, Pocilloporidae, Poritidae, Faviidae, Pectiniidae, and Fungiidae) from Vietnam were analyzed for fatty acid (FA) composition. Except for the Poritidae species, total lipids of the corals had the same set of FAs, about 50% of them being unsaturated acids. Some coral families had high levels of characteristic FAs: 20:3(n-6), 20:4(n-3), and 22:6(n-3) in Pocilloporidae; 18:1(n-9) and 22:6(n-3) in Poritidae; and 18:3(n-6) and 22:5(n-3) in Faviidae. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…Our present (Fig. 3) and previous results (Imbs et al 2007a) showed that at least 5 scleractinian families (Acroporidae, Faviidae, Fungiidae, Pocilloporidae, and Poritidae) had a distinct PUFA composition. In spite of lipid variations caused by food sources, coral species within of some scleractinian families, and even some genera, had similar metabolisms and accumulation of PUFA.…”
Section: Distribution Of Fatty Acidssupporting
confidence: 82%
See 4 more Smart Citations
“…Our present (Fig. 3) and previous results (Imbs et al 2007a) showed that at least 5 scleractinian families (Acroporidae, Faviidae, Fungiidae, Pocilloporidae, and Poritidae) had a distinct PUFA composition. In spite of lipid variations caused by food sources, coral species within of some scleractinian families, and even some genera, had similar metabolisms and accumulation of PUFA.…”
Section: Distribution Of Fatty Acidssupporting
confidence: 82%
“…Recently, the set of 10 PUFA was successfully used as PCA variables for chemotaxonomic investigations of reef-building corals (Imbs et al 2007a). ANOVA tests for each possible pair from the 4 families indicated that there were no differences (p > 0.05) in 20:4n-6, 18:3n-6, and 18:4n-3, but most of the pairs differed in C 18 -20 monoenoic FA.…”
Section: Hexacoralsmentioning
confidence: 99%
See 3 more Smart Citations